Socio-Pedagogical Support for the Development of Resilience in Children and Youth Affected by War - Amelina, Viktoria; Bybyk, Daria (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article addresses the issue of socio-pedagogical support for the development of resilience among Ukrainian youth in the post-war period, a challenge that has become particularly relevant amid large-scale social transformations and the urgent need to restore the country’s human potential. The aim of the study is to substantiate and define effective technologies of socio-pedagogical support aimed at fostering resilience in youth under post-war challenges. The research objectives include revealing the essence and structure of the concept of “youth resilience”, analyzing scientific approaches and factors influencing its development, determining the role of socio-pedagogical support, characterizing technologies applicable in the recovery period, and developing an algorithm for the practical implementation of support. The research methodology is based on a combination of quantitative and qualitative methods, which ensured a multidimensional analysis. Descriptive, explanatory, and prognostic methods were applied, along with theoretical analysis, comparison, and synthesis of scientific sources. The scientific novelty of the article lies in systematizing the specific features of the process of developing youth resilience, considering the challenges of the wartime and post-war periods, clarifying the factors that influence its formation, and defining a set of socio-pedagogical support technologies that contribute to the development of internal resources and social activity. The research findings confirm that the development of resilience is a key condition for successful socialization and adaptation of youth. The study emphasizes the multi-component nature of resilience, which includes cognitive, emotional, and behavioural strategies. It was established that effective support technologies should combine individual psychological support, group training, development of emotional intelligence, stress management skills, and the creation of a supportive educational environment. An innovative aspect is the emphasis on integrating digital tools and remote support, enabling the reach of the program to wider groups of young people, including those in areas with limited infrastructure.